Clearing the Plains and Changing the National Conversation: James Daschuk’s Clearing the Plains as a Work of Popular and Public History - Mosby, Ian (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2015)
This essay assesses the impressive public reaction to James Daschuk’s Clearing the Plains and offers some possible explanations for its success as a work of both academic and popular history.